The Influence of Pentagon Fraud on Financial Reporting Fraud - Gerardus Alan Darmasaputra; Teodora Winda Mulia (Universitas KH. Abdul Chalim Mojokerto, 2025)
Financial statement fraud involves the intentional alteration of financial records by management or related individuals to distort the company’s true financial position, with the purpose of misleading stakeholders for either personal gain or organizational advantage. This research explores the combined and separate effects of several variables including financial stability, external pressure, financial targets, opportunities, changes in auditors and directors, as well as the display of the CEO’s photograph on the likelihood of financial statement fraud among infrastructure firms listed on the Indonesia Stock Exchange during the 2019–2023 period. The research population includes all infrastructure firms publicly traded on the IDX during that period, from which 145 company-year observations were obtained using a purposive sampling approach. The study employs descriptive statistical analysis and logistic regression techniques, with data processed using SPSS version 27. The results indicate that the collective impact of all investigated variables shows a statistically significant association with the occurrence of financial statement fraud. On an individual level, opportunity and auditor turnover have a positive and significant influence on fraudulent activities. In contrast, financial stability, external pressure, financial targets, and the presence of the CEO’s photo do not demonstrate a meaningful effect on the probability of fraud. Future investigations are encouraged to incorporate alternative proxy variables such as audit opinions or total accruals to better explore the dimensions of the Fraud Pentagon in the context of financial misreporting.